Pengembangan Media Scrapbook pada Mata Pelajaran IPS Materi Keragaman Suku Bangsa Untuk Kelas IV SD - Destriani Destriani; Murjainah Murjainah; Mega Prasrihamni (STKIP Andi Matappa Pangkep, 2022)
This development research aims to produce a scrapbook of material on ethnic diversity that is valid, practical, and has potential effects for fourth grade elementary school students. The method used in this research is a research and development method. The scrapbook media developed used the Alessi and Trollip model with three stages, namely planning, design, and development. Data collection techniques using questionnaires and learning outcomes tests. The data were analyzed quantitatively and qualitatively. The results showed that the development of scrapbook media in social studies subjects on ethnic diversity material carried out by researchers was declared valid based on the assessment of the validators consisting of 3 lecturers assessed from all aspects, namely construct, content, and language with the percentage obtained 95.8%. , the scrapbook media in the social studies subject matter of ethnic diversity that has been developed is declared practical based on the student response questionnaires obtained an average of 91.6% in the one to one stage, and 93.9% in the small group stage, and scrapbook media in social studies subjects, the developed ethnic diversity material is declared effective or has a potential effect with a percentage gain of 80%.